An evaluation of ultrasonic arrays for the static and dynamic measurement of wheel–rail contact pressure and area. (October 2020) - Brunskill, Henry; Hunter, Andy; Zhou, Lu; Dwyer Joyce, Rob; Lewis, Roger
The interfacial contact conditions between a railway vehicle wheel and the rail are paramount to the lifespan, safety and smooth operation of any rail network. The wheel–rail interface contact pressure and area conditions have been estimated, calculated and simulated by industry and academia for many years, but a method of accurately measuring dynamic contact conditions has yet to be realised. Methods using pressure-sensitive films and controlled air flow have been employed, but both are limited. Ultrasonic reflectometry is the term given to active ultrasonics in which an ultrasonic transducer is mounted on the outer surface of a component and a sound wave is generated. This ultrasonic wave packet propagates through the host medium and reflects off the contacting interface of interest. The reflected waveform is then detected and contact area and interfacial stiffness information can be extracted from the signal using the quasi-static spring model. Stiffness can be related to contact pressure by performing a simple calibration procedure. Previous contact pressure measurement work has relied on using a focusing transducer and a two-dimensional scanning arrangement which results in a high-resolution image of the wheel–rail contact, but is limited to static loading of a specimen cut from a wheel and rail. The work described in this paper has assessed the feasibility of measuring a dynamic wheel–rail contact patch using an array of 64 ultrasonic elements mounted in the rail. Each element is individually pulsed in sequence to build up a linear cross-sectional pressure profile measurement of the interface. These cross-sectional, line measurements are then processed and collated resulting in a two-dimensional contact pressure profile. Measurements have been taken at different speeds and loads.